Autophagy in Adipocyte Browning: Emerging Drug Target for Intervention in Obesity - Ro, Seung-Hyun; Jang, Yura; Bae, Jiyoung; Kim, Isaac M.; Schaecher, Cameron; Shomo, Zachery D. (Frontiers in Physiology, 2019)
Autophagy, lipophagy, and mitophagy are considered to be the major recycling processes for protein aggregates, excess fat, and damaged mitochondria in adipose tissues in response to nutrient status-associated stress, oxidative stress, and genotoxic stress in human body. Obesity with increased body weight is often associated with white adipose tissue hypertrophy and hyperplasia and/or beige/brown adipose tissue atrophy and aplasia, which significantly contribute to the imbalance in lipid metabolism, adipocytokine secretion, free fatty acid release, and mitochondria function. In recent studies, hyperactive autophagy in white adipose tissue was observed in obese and diabetic patients, and inhibition of adipose autophagy through targeted deletion of autophagy genes in mice improved anti-obesity phenotypes. In addition, active mitochondria clearance through activation of autophagy was required for beige/brown fat whitening – that is, conversion to white fat. However, inhibition of autophagy seemed detrimental in hypermetabolic conditions such as hepatic steatosis, atherosclerosis, thermal injury, sepsis, and cachexia through an increase in free fatty acid and glycerol release from white adipose tissue. The emerging concept of white fat browning ‒ conversion to beige/brown fat ‒ has been controversial in its anti-obesity effect through facilitation of weight loss and improving metabolic health. Thus, proper regulation of autophagy activity fit to an individual metabolic profile is necessary to ensure balance in adipose tissue metabolism and function and to further prevent metabolic disorders such as obesity, diabetes, cardiovascular disease, and cancer. In this review, we summarize the effect of autophagy in adipose tissue browning in the context of obesity prevention and its potential as a promising target for the development of anti-obesity drugs.